Conditions for feedbacks between geomorphic and vegetation dynamics on lateral moraine slopes: a biogeomorphic feedback window. Issue 3 (25th November 2015) - Eichel, Jana; Corenblit, Dov; Dikau, Richard
Abstract: Little Ice Age lateral moraines represent one of the most important sediment storages and dynamic areas in glacier forelands. Following glacier retreat, simultaneous paraglacial adjustment and vegetation succession affect the moraine slopes. Geomorphic processes (e.g. debris flows, interrill erosion, gullying, solifluction) disturb and limit vegetation development, while increasing vegetation cover decreases geomorphic activity. Thus, feedbacks between geomorphic and vegetation dynamics strongly control moraine slope development. However, the conditions under which these biogeomorphic feedbacks can occur are insufficiently understood and major knowledge gaps remain. This study determines feedback conditions through the analysis of geomorphic and vegetation data from permanent plots in the Turtmann glacier foreland, Switzerland. Results from multivariate statistical analysis (i) confirm that Dryas octopetala L. is an alpine ecosystem engineer species which influences geomorphic processes on lateral moraines and thereby controls ecosystem structure and function, and (ii) demonstrate that biogeomorphic feedbacks can occur once geomorphic activity sufficiently decreases for D. octopetala to establish and cross a cover threshold. In the subsequent ecosystem engineering process, the dominant geomorphic processes change from flow and slide to bound solifluction. Increasing slope stabilization induces a decline in biogeomorphic feedbacks and the suppression of D. octopetala by shrubs. We conceptualize this relationship between process magnitude, frequency and species resilience and resistance to disturbances in a 'biogeomorphic feedback window' concept. Our approach enhances the understanding of feedbacks between geomorphic and alpine vegetation dynamics on lateral moraine slopes and highlights the importance of integrating geomorphic and ecological approaches for biogeomorphic research. Copyright © 2015 John Wiley & Sons, Ltd.